G141(P) Developmental Stages of Early Feeding. (7th April 2014) - Harris, G
Abstract : Introduction: Developmental milestones can be important markers of typical child development. Parents often ask health professionals (HCPs) when their child can be expected to attain feeding and drinking related skills and develop specific food related preferences. Parents also want to know if it is 'normal' for their child to be reluctant to accept certain tastes, or which food textures. Advice is often conflicting based on myth, inaccurate interpretation of evidence, or on an evidence base which has long been challenged. Objective: Produce practical guidance describing evidence-based developmental stages relating to feeding, eating and drinking to inform: advice from HCPs about infant feeding skills and feeding and eating behaviour advice from HCPs about good practice for parents in establishing positive mealtimes parents and HCPs about when there might be a need for specialist Methodology: A comprehensive literature review was carried out from pre birth to age 4 years. These searches included topics such as oral-motor skills relating to feeding, acceptance of lumpy, textured, solid foods, and the development of the gag response. External consultation was undertaken with health visitors, speech and language therapists, psychologists and paediatricians who are experts in their field to validate the findings. Results: Skills related to feeding and eating: interaction with others, imitation of others, facial expression, smells and tastes, motor development of feeding skills Feeding specific skills: oral motor development, self-feeding and eating preferences Taste and food preferences: acceptance, rejection and texture progression stages Appetite regulation: signalling hunger, satiety, dislike and regulation Skills within each area were then plotted against a timeframe to define and illustrate the developmental stage. Visual representations of each stage were key to keep information practical and with the end user top of mind. Conclusion: Evidenced-based guidelines on the development of feeding, eating and drinking skills and the development of food preferences in infants and toddlers are not only key to reassuring parents about their child's development, they are also critical in helping parents and carers instil healthy eating habits from as early on in life as possible.